2011
DOI: 10.4103/2229-516x.81972
|View full text |Cite
|
Sign up to set email alerts
|

Bioenhancers from mother nature and their applicability in modern medicine

Abstract: Concept of bioenhancers or biopotentiators was first time reported in 1929 by Bose. A bioenhancer is an agent capable of enhancing bioavailability and efficacy of a drug with which it is co-administered, without any pharmacological activity of its own at therapeutic dose used. Development and consequent isolation of these molecules, such as piperine and quercetin, is considered as scientific breakthrough. A fixed drug combination (Risorine) of rifampicin, isoniazid, and piperine is the result of this research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 31 publications
0
49
0
2
Order By: Relevance
“…However in Siddha system of medicine, adjuvant also occupies an important place in medication and a single drug can be used for a variety of ailments by changing its adjuvants (Subbarayappa, 1997). Bioenhancers (or) biopotentiators are the chemicals that enhance the bioavailability, tissue distribution, and the efficacy, especially for the drugs with poor oral bioavailability; they decrease the adverse effects in the process (Randhawa et al, 2011). The biopotentiators might act through enhancing the absorption, by acting as prodrugs or by inhibiting P-glycoprotein medicated efflux (Kang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However in Siddha system of medicine, adjuvant also occupies an important place in medication and a single drug can be used for a variety of ailments by changing its adjuvants (Subbarayappa, 1997). Bioenhancers (or) biopotentiators are the chemicals that enhance the bioavailability, tissue distribution, and the efficacy, especially for the drugs with poor oral bioavailability; they decrease the adverse effects in the process (Randhawa et al, 2011). The biopotentiators might act through enhancing the absorption, by acting as prodrugs or by inhibiting P-glycoprotein medicated efflux (Kang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The combination of aqua-ethanolic extract of Camellia sinensis with ertapenem or meropenem showed maximum augmentative potential at 50 μg/mL and 100 μg/mL, respectively, with 5 fold decrease in MICs [84]. Bioenhancers are combined with antibiotics like tetracycline combined with drug loperamide to enhance the bioavailability and efficacy of drug by increasing its permeability, without its own pharmacological activity [85,86]. Also, Cow Urine Distillate (CUD) enhances rifampicin activity against E. coli by 57 times as well as against gram positive bacteria by 311 times [85].…”
Section: Interaction Between Herbal Drugs and Antibioticsmentioning
confidence: 99%
“…Bioenhancers are combined with antibiotics like tetracycline combined with drug loperamide to enhance the bioavailability and efficacy of drug by increasing its permeability, without its own pharmacological activity [85,86]. Also, Cow Urine Distillate (CUD) enhances rifampicin activity against E. coli by 57 times as well as against gram positive bacteria by 311 times [85]. Some of the drug interaction examples will be shown in Table 2.…”
Section: Interaction Between Herbal Drugs and Antibioticsmentioning
confidence: 99%
“…It has antifungal, anthelmintic, antineoplastic action, is useful in hypersensitivity reactions and in numerous other diseases including increasing the life-span of a person. Recent researches have shown that CU is an immune-enhancer also [7-9]. Therapeutic properties of CU have been validated by modern science also.…”
Section: Introductionmentioning
confidence: 99%